The Influence of Business Analysis and Environmental Orientation on Green Business Strategy with Green Innovation as a Mediation Variable in SMEs that are members of the Sibakul Jogja Platform in Yogyakarta City - Sari Puaspita, Irinne Sukma; sabihaini, Sabihaini; Kristanto, Heru (International Journal Labs, 2024)
This study aims to determine the effect of business analysis and environmental orientation on green business strategy with green innovation as a mediating variable in SMEs incorporated in the SiBakul Jogja platform in Yogyakarta City. This research uses quantitative descriptive methods. The sample in this study was 100 SMEs. The sampling technique used purposive sampling. The data analysis method used in the study was Partial Least Squares (PLS). The results of this study are business analysis has a positive and significant effect on green business strategy. Environmental orientation has a positive and significant effect on green business strategy. Business analysis has a positive and significant effect on green innovation. Environmental orientation has a positive and significant effect on green innovation. Green innovation has a positive and significant effect on green business strategy. Green innovation positively and significantly mediates business analysis on green business strategy. Green innovation positively and significantly mediates environmental orientation on green business strategy.